Miliary Tuberculosis in an Immunocompetent Patient Presenting with Tuberculous Meningoencephalitis Complicated by Hydrocephalus and Seizures - Ahmed Alsahlawi; Mohanad Alkuwaiti; Mohammed Dhafer; Mudar Alwazzeh; Albaraa Juraybi; Sara M. Alwarthan; Shaya AlQahtani; Marwan Jabr Alwazzeh (Journal of Global Infectious Diseases, 2025)
Miliary tuberculosis (MTB) is a disseminated form of tuberculosis (TB) arising from the lymphohematogenous dissemination of Mycobacterium tuberculosis bacilli followed by millet seed-sized tuberculous foci. It mainly affects immunocompromised patients and can lead to severe complications or even death. The clinical manifestation is diverse and depends on the organ affected, the patient’s immune status, and the possible involvement of the central nervous system (CNS). Hence, this case report presents a case of an immunocompetent male with a decreased level of consciousness and convulsions requiring admission to the intensive care unit. The patient was diagnosed with MTB, meningoencephalitis, hydrocephalus, and severe hyponatremia. He subsequently improved after a short period of initiation of anti-TB medications. This report also highlights the clinical features of MTB and reviews the literature on associated CNS complications of MTB.